THE EFFECT OF ISLAMIC FINANCIAL LITERACY ON SAVINGS DECISIONS IN ISLAMIC BANKS WITH CUSTOMER VALUE MEDIATION (CASE STUDY: MEDAN CITY) - Ihsan Rambe; Fathurrahman Djamil; Koesmawan; Didin Saepudin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This study aims to test, analyze and reveal the important role of Islamic financial literacy in improving saving decisions both directly and by mediating customer value at the Islamic banks. Customer value as an emotional bond that arises between customers and Islamic banks as intermediaries (mediation), is expected to be a stimulation for Islamic financial literacy to influence the decision to save in an Islamic bank. Previous research Bayar, et al (2017), Antara, et al (2017) hopes that literacy can advance Islamic finance. This research confirms that Islamic financial literacy can improve saving decisions at Islamic banks in Medan. The methods used in this study are descriptive and verifiable methods with a quantitative approach. The data analysis technique uses Partial Least Square (PLS) to see the structural model along with the relationship and influence of Islamic financial literacy and customer value and saving decisions in Islamic banks. This research proves that directly and indirectly Islamic financial literacy plays an important role in improving savings decisions in Islamic banks in Medan. Emotional ties also help Islamic financial literacy to improve savings decisions in Islamic banks in Medan.